Assessment of some mechanical properties of Imprelon® and Duran® thermoplastic Biostar machine sheets in comparison with some types of acrylic resins - Mustafa F Mohammed; Salah A Mohammad (College of Dentistry/ University of Baghdad, 2014)
Background: Imprelon® Biostar foils are new alternative tray material that has become increasingly popular because oftheir several advantages. Also, (Duran®) is another type of Biostar foils which is used in splint therapy. This study assessed some mechanical properties of these two types Biostar sheets in comparison with some types of acrylic resins used for construction of trays and splints. Materials and Methods: A total of 150 specimens were prepared, 30 specimens for each test, 10 for each group material in order to assess some mechanical properties of the Imprelon® Biostar foil (dimension stability, surface roughness and shear bond strength of Imprelon® materialto zinc oxide impression material) and compare them to that of the other tray materials (autopolymerized and VLC) resin materials. Also to assess the mechanical properties (wear rate and transverse strength) of the Duran® Biostar Foil and compared them with that of the other splints materials (heat-cure acrylic and VLC) resins. Results:The results showed highly significant differences at P